2012
DOI: 10.1007/s11999-011-2089-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Morphology of the Knee Reveals Ethnic Differences

Abstract: BackgroundStudies have demonstrated sex differences in femoral shape and quadriceps angle raising a question of whether implant design should be sex-specific. Much of this research has addressed shape differences within the Caucasian population and little is known about differences among ethnic groups.Questions/purposesWe therefore asked: Do shape differences in the distal femur and proximal tibia exist among different ethnic groups and between the sexes in each ethnic population? And if ethnic differences exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
177
2
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(201 citation statements)
references
References 26 publications
17
177
2
5
Order By: Relevance
“…For this reason, observations of the present study suggest that the size of the sulcus angle cannot determine sex in Malawians. This supports earlier studies that have reported that sexual dimorphism is race and population specific 10,14, [20][21][22][23] . Additionally, it has been observed in our study that the mean femoral sulcus angles for males combined and females combined are 142. .…”
supporting
confidence: 92%
“…For this reason, observations of the present study suggest that the size of the sulcus angle cannot determine sex in Malawians. This supports earlier studies that have reported that sexual dimorphism is race and population specific 10,14, [20][21][22][23] . Additionally, it has been observed in our study that the mean femoral sulcus angles for males combined and females combined are 142. .…”
supporting
confidence: 92%
“…Moreover, the differences were not uniform, as the difference in some measurements had a broader range than other measurements. The main findings was the larger values for the male tibias compared to the female tibias, which is in agreement with data described in the literature (Mahfouz et al, 2012;Lim et al, 2013;Gandhi et al). * Statistically significant difference between male and female tibias using Mann-Whitney test ** Statistically significant difference between male and female tibias using Student's t-test Table I.…”
Section: Discussionsupporting
confidence: 90%
“…This may be attributed to the splay of the medio-lateral dimension of the distal femur and proximal tibia and comparatively delayed presentation for replacement from the onset of symptoms. 18,19 80% of the operated knees had fixed bearing curved plus insert which might have been the preferred choice of the operating surgeon to enhance stability. 41% of the operated knees had size 10 polyethylene tibial insert followed by 12.5 size in 22.9%.…”
Section: Discussionmentioning
confidence: 99%